Pengembangan Skala Keyakinan Irasional dalam Penulisan Skripsi - Rahman, Diniy Hidayatur (Jurnal Kajian Bimbingan dan Konseling, 2019)
Previous studies have shown that irrational beliefs contribute significantly to the procrastination, including the thesis-writing procrastination. Unfortunately, there are no scales that specifically can measure the beliefs in the thesis writing context. Therefore, this study aimed to develop and validate a scale called the Skala Keyakinan Irasional dalam Penyusunan Skripsi (SKI-S). The scale was developed based on irrational belief construct proposed by Albert Ellis in the context of thesis writing. To achieve the aim, the study applied a research and development design involving four steps: (1) defining the construct; (2) developing the measurement model; (3) carrying out confirmatory factor analysis; and (4) checking the validity of the measurement model. 200 undergraduate students taking their 9th to 14th semester were involved in the study. 86 items were successfully validated which were classified into demandingness subscale (16 items); catastrophizing subscale (20 items); self-depreciation subscale (17 items); and low frustration tolerance subscales (20 items).